Seasonality of Coastal Picophytoplankton Growth, Nutrient Limitation, and Biomass Contribution - Alegria Zufia, Javier; Farnelid, Hanna; Legrand, Catherine (Frontiers in Microbiology, 2021)
Picophytoplankton in the Baltic Sea includes the simplest unicellular cyanoprokaryotes (Synechococcus/Cyanobium) and photosynthetic picoeukaryotes (PPE). Picophytoplankton are thought to be a key component of the phytoplankton community but their seasonal dynamics and relationships with nutrients and temperature are largely unknown. We monitored pico- and larger phytoplankton at a coastal site in Kalmar Sound (K-Station) weekly during 2018. Among the cyanoprokaryotes, phycoerythrin-rich (PE-rich) Synechococcus dominated in spring and summer while phycocyanin-rich (PC-rich) picocyanobacteria dominated during autumn. PE-rich Synechococcus and PC-rich picocyanobacterial abundances peaked during summer (1.1×105 and 2.0×105 cells mL-1) while PPE reached highest abundances in spring (1.1×105 cells mL-1). PPE was the main contributor to the total phytoplankton biomass (up to 73%). To assess nutrient limitation, bioassays with combinations of nitrogen (NO3 or NH4) and phosphorus additions were performed. PE-rich Synechococcus and PC-rich picocyanobacteria growth was mainly limited by nitrogen, with a preference for NH4 at 15-19°C. The three groups had distinct seasonal dynamics and different temperature niches: 10°C and 17-19°C for PE-rich Synechococcus, 13-16°C for PC-rich picocyanobacteria and 11-15°C for PPE. We conclude that picophytoplankton contribute significantly to the carbon cycle in the coastal Baltic Sea and underscore the importance of investigating functional groups to assess the consequences of the combination of high temperature and NH4 in a future climate.